Half-wave-crystal channeling of relativistic heavy ions at super-FRS GSI/FAIR - Bogdanov, O. V.; Pivovarov, Yu. L.; Tukhfatullin, T. A.; Geissel, H.; Kuzminchuk-Feuerstein, N.; Purushothaman, S.; Scheidenberger, Christoph (Nuclear instruments and methods in physics research. Section B : Beam interactions with materials and atoms)
The computer simulations of relativistic heavy ions channeling through the half-wavelength crystal showed the similarity of trajectories and angular distributions for ions with close ratios of the mass number A and the ion charge Ze. We studied the deflection efficiency of 300 MeV/u and 30 GeV/u 129Xe, 208Pb, 238U ions by a single tungsten half-wavelength crystal. In addition, we showed that the assembly of two sequentially placed and rotated by the critical channeling angle half-wavelength crystals increases twice the deflection angle.